Risk of preterm delivery with increasing depth of excision for cervical intraepithelial neoplasia in England: nested case-control study. (5th November 2014) - Castanon, Alejandra; Landy, Rebecca; Brocklehurst, Peter; Evans, Heather; Peebles, Donald; Singh, Naveena; Walker, Patrick; Patnick, Julietta; Sasieni, Peter
Abstract : Objective To determine the association between depth of excision of cervical intraepithelial neoplasia and risk of preterm birth. Design Case-control study nested in record linkage cohort study. Setting 12 hospitals in England. Participants From a cohort of 11 471 women with at least one histological sample taken at colposcopy and a live singleton birth (before or after colposcopy), 1313 women with a preterm birth (20-36 weeks) were identified and frequency matched on maternal age at delivery, parity, and study site to 1313 women with term births (38-42 weeks). Main outcome measures Risk of preterm birth and very/extreme preterm birth by depth of excisional treatment of the cervical transformation zone. Results After exclusions, 768 preterm births (cases) and 830 term births after colposcopy remained. The risk of preterm birth was no greater in women with a previous small (<10 mm) excision (absolute risk 7.5%, 95% confidence interval 6.0% to 8.9%) than in women with a diagnostic punch biopsy (7.2%, 5.9% to 8.5%). Women with a medium (10-14 mm) (absolute risk 9.6%; relative risk 1.28, 0.98 to 1.68), large (15-19 mm) (15.3%; 2.04, 1.41 to 2.96), or very large (≥20 mm) excision (18.0%; 2.40, 1.53 to 3.75) had a higher risk of preterm delivery than those with small excision. The same pattern was seen in 161 women with very/extremely preterm births (20-31 weeks) and with increasing volume excised. Most births were conceived more than three years after colposcopy, and the risk of preterm delivery did not seem to depend on time from excision to conception. Conclusions The risk of preterm birth is at most minimally affected by a small excision. Larger excisions, particularly over 15 mm or 2.66 cm 3, are associated with a doubling of the risk of both preterm and very preterm births. The risk does not decrease with increasing time from excision to conception. Efforts should be made to excise the entire lesion while preserving as much healthy cervical tissue as possible. Close obstetric monitoring is warranted for women who have large excisions of the cervical transformation zone.